TOPONYMIC ANALYSIS OF ADMINISTRATIVE REGIONS AND ADMINISTRATIVE CENTERS OF ANDIJAN REGION (Scientific journal of the Fergana State University, 2024)
The article examines the importance of toponymy, which is considered a modern branch of geography, in the analytical study of toponyms in relation to such disciplines as geography and history. The study of geographical names and their differences from each other is a rather complex process, and the confusion in them of the concepts of categories (city, region, mountain, desert, etc.) creates difficulties in their study. The article attempts to shed light on the names of the districts of the Andijan region, their origin and content, as well as to analyze the data left by foreign and domestic scientists about the names of places in the region.